Characteristics and Control Mechanism of Lacustrine Shale Oil Reservoir in the Member 2 of Kongdian Formation in Cangdong Sag, Bohai Bay Basin, China - Xu, Qilu; Zhao, Xianzheng; Pu, Xiugang; Han, Wenzhong; Shi, Zhannan; Tian, Jinqiang; Zhang, Bojie; Xin, Bixiao; Guo, Pengfei (Frontiers in Earth Science, 2021)
The significance of lacustrine shale oil has gradually become prominent. Lacustrine shale has complex lithologies, and their reservoir properties are quite various. The multi-scale pore structure of shale controls the law of shale oil enrichment. Typical lacustrine shale developed in the Member 2 of Kongdian Formation in Cangdong sag, Bohai Bay Basin. The lithofacies and multi-scale storage space of this lacustrine shale have been systematically studied. 1. The mineral composition is quite different, and the lithofacies can be summarized into siliceous, carbonate and mixed types. The rock structure can be summarized into laminated, layered, and massive types. 2. The pores are diverse and multi-scale. Interparticle pores contribute the main storage space, especially the interparticle pores of quartz and dolomite. 3. The physical properties of the massive shales is relatively inferior to those of layered and laminatedtypes, and it presents the characteristics of " laminated >layered > massive ". The developed laminae can significantly improve the space and seepage capacity of lacustrine shale. 4. Clay minerals provide the main nano-scale storage space, but they are often filled in pores and reduces the shale brittleness, which have destruction effects.